Pemanfaatan Jeroan Ikan Dengan Limbah Kulit Jagung Sebagai Pakan Alternatif Ikan Lele - Ion Tarsardo Sianturi; Fajar Panuntun; Fransiska Indang (Clarias : Jurnal Perikanan Air Tawar, 2022)
The demand for freshwater consumption fish, especially catfish, is so fast that the aquaculture sector needs to be increased again. The supporting factor in the success of aquaculture is feed, where feed for catfish cultivation on Timor Island, NTT is still much more expensive than on the island of Java, this is an inhibiting factor for the success of cultivation on Timor Island. These problems can be overcome by making independent feed. The purpose of this activity is to determine the potential of local raw materials or waste in Timor Island as raw materials for making fish feed. The method used is a descriptive method where research describes the phenomenon or individual characteristics, the situation accurately in a certain group. Based on the results obtained that the waste on the island of Timor, namely fish offal and corn husks can be used as raw materials for making feed and has a fairly good buoyancy shown by being able to float for more than 5 minutes.